An Analysis of Students’ Understanding in using Simple Present Tense for Writing Routines at SMP Negeri 06 Kayan Hilir in Academic Year 2021/2022 - Caroline Caroline; Henry Elisa (SEMINAR NASIONAL PENINGKATAN MUTU PENDIDIKAN, 2022)
The aim of the research is to know the students’ understanding in using simple present in writing routines and to know the obstacles faced by students in writing routines by using simple present tense at SMP Negeri 06 Kayan Hilir. The focus of this research is on students' understanding in using nouns, verbs, adjectives, and adverbs for writing routines. The method used in this research is a qualitative. The data collected by using questionnaire, interview, and documentation as techniques. The researcher used questionnaire, interview guidelines, and students' writing products as instrumentations. The researcher interviewed the English teacher and the students in this research. The documentation includes the data which are students writing product, and all the photo of the research. The subjects of the research are 35 students. The research results found from analyzed the students’ writing product of students understanding in using noun, verb, and adverb was higher than students’ understanding in using adjective. Based on the results of the questionnaire, it can be seen that the students' understanding included with the good category.